The Qual-Quant Distinction (Debate): Understanding the Phenomena - Poudel, Tara N (Review of Knowledge Economy, 2014)
Because the qualitative and quantitative data can be analyzed by both qualitative and quantitative methods, some scholars argue that the combination of theme can be more effective but others argues that the distinction between qualitative and quantitative data have certain utility, though most people draw to hard a distinction. Although, the quantitative-qualitative distinction can lead to some sorts of confusions due to their distinct ontological and measurement related issues; the qual-quant distinction debate is philosophical, not methodological. Hence this paper discusses about the philosophical and practical issues on qual-quant distinction and the interpretation of qualitative and quantitative data in the form of each other.